Environmental Education for Solid Waste Management (GnosisWisdom, 2022)
In 2014, the VII Ibero-American Congress on Environmental Education was held in Peru, which was an event to present reflective and critical conferences on environmental education policies in Ibero-American countries, thus contributing to education for the sustainability of life and to raising the awareness of an environmentally aware population. The present bibliographical review of the most recent research on environmental education to contribute to the integrated management of solid waste is based on these experiences, with the aim of obtaining relevant information related to environmental awareness in order to counteract environmental pollution caused by solid waste, For this purpose, a hermeneutic analysis was made of the references available in the databases SciELO, Redalyc, Science Direct and others, using the terms environmental awareness, environmental pollution and solid waste as descriptors, emphasizing the objectives, categories, principles, proposals and policies of environmental education. It was found that, after many years of indiscriminate use of pesticides, damage has been caused to the environment, especially to the agricultural sector in contaminated areas, and water treatment techniques are being used with chemical inputs with side effects such as the appearance of multiple oxidizing agents responsible for the mineralisation of pollutants in herbicides. It was concluded that awareness, knowledge and human behavior directly affect solid waste management.
Keywords: Environmental awareness; environmental sustainability; pollution; solid waste